2015
DOI: 10.1017/s0033291715002317
|View full text |Cite
|
Sign up to set email alerts
|

Who are gynandromorphophilic men? Characterizing men with sexual interest in transgender women

Abstract: Results provide clear evidence that GAMP men are not homosexual. They also indicate that GAMP men are especially likely to eroticize the idea of being a woman.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…In most research, the majority of bisexual-identified men showed genital arousal patterns that resembled those of homosexual men (Bailey, Rieger, & Rosenthal, 2011;Freund, Langevin, & Barlow, 1974;Rieger, Chivers, & Bailey, 2005;Tollison, Adams, & Tollison, 1979). Moreover, a sub-group of bisexual-identified men showed heterosexual arousal; yet, on average, none showed bisexual arousal (Hsu, Rosenthal, Miller, & Bailey, 2016;Rieger et al, 2005). In sum, these particular findings suggest that many bisexual-identified men are sexually aroused to one sex only, thus, show monosexual arousal, similar to most heterosexual and homosexual men.…”
Section: Bisexual Men With Bisexual and Monosexual Genital Arousal Pamentioning
confidence: 88%
“…In most research, the majority of bisexual-identified men showed genital arousal patterns that resembled those of homosexual men (Bailey, Rieger, & Rosenthal, 2011;Freund, Langevin, & Barlow, 1974;Rieger, Chivers, & Bailey, 2005;Tollison, Adams, & Tollison, 1979). Moreover, a sub-group of bisexual-identified men showed heterosexual arousal; yet, on average, none showed bisexual arousal (Hsu, Rosenthal, Miller, & Bailey, 2016;Rieger et al, 2005). In sum, these particular findings suggest that many bisexual-identified men are sexually aroused to one sex only, thus, show monosexual arousal, similar to most heterosexual and homosexual men.…”
Section: Bisexual Men With Bisexual and Monosexual Genital Arousal Pamentioning
confidence: 88%
“…While many people use the terms transman and transwoman to identify transgendered persons, others refer to trans individuals as transsexuals, transwomen, t-girls or those with trans experience. Other, often offensive terms such as he-she, lady boy, chicks with dicks and she-male are also used, often highlighting the role of the real or imagined penis of the trans-identified person (Clark-Flory, 2011;Hsu, Rosenthal, Miller, & Bailey, 2016). Language can be used to label groups for classification or to devalue them.…”
Section: Trans-attraction Perspectives From the Medical And Scholarlymentioning
confidence: 99%
“…A common belief is that trans-attracted men are closeted gay men who are fearful of being outed, so they find solace in women who also have a penis (Notario, 2018). Hsu, Rosenthal, Miller and Bailey (2016) challenged that myth, developing a study to compare men's claimed sexual attraction with the results of a device that measured sexual arousal. Findings reflected the men's arousal patterns matched their declarations; in particular, men who claimed attraction to trans women showed high arousal when watching transgender women, moderate arousal with cisgender women and very low arousal when watching men have sex with men (Hsu, et al, 2016).…”
Section: Shamementioning
confidence: 99%
See 2 more Smart Citations